Musica, scienziato! Trilogia di monologhi scientifantastici - Dei, Luigi (Firenze University Press, 2014)
Musica, scienziato!, a work that cannot be reduced to pre-existing models, establishes a new literary genre, the scientifantasia, which, although part of a literary tradition which has included eminent figures such as the acrobatic engineer Gadda and the chemist Levi, is here presented in a totally new physiognomy. The scientist-writer, Narrator of the monologues, becomes a musical storyteller that makes up stories through the languages of his time, and the 'scientific word' ends up "exorcising the evil of history and the weight of existence" in order to soften and redeem them, placing them within the range of knowledge and expression without which, quoting the Shakespearean lines recited at the end of Revealing Ravel, man is "fit for treasons, stratagems, and spoils. / The motions of his spirit are dull as night, / and his affections dark as Erebus". Revealing Ravel: science tells Boléro Musical play for narrative voice, multimedia and orchestra with music by Maurice Ravel Symphonic Orchestra "L. Cherubini" of the Florence Conservatory conducted by Paolo Ponziano Ciardi From Schubert to De André: the mysteries of the voice in music Show for narrative voice, multimedia and vocal music by and with Luigi Dei Watch the video on YouTube From Baroque to Rock: along with Darwin in the nature of musical species Monologue for narrative voice, multimedia and music of various kinds by and with Luigi Dei Watch the video on YouTube